The effect of lncRNA‐ARAP1‐AS2/ARAP1 on high glucose‐induced cytoskeleton rearrangement and epithelial–mesenchymal transition in human renal tubular epithelial cells. Issue 7 (24th January 2020) - Li, Lulu; Xu, Li; Wen, Si; Yang, Ying; Li, Xin; Fan, Qiuling
Abstract: The epithelial–mesenchymal transition (EMT) plays an important role in diabetic renal fibrosis. The ARAP1 gene is located near risk alleles for Type 2 diabetes, and its function has been linked to cytoskeleton rearrangement, Golgi apparatus remodeling, and endocytic trafficking of membrane receptors. The role of ARAP1 and its antisense RNA, ARAP1‐AS2, in the pathogenesis of diabetes is unclear. To clarify the roles of ARAP1 and its antisense RNA in diabetes and related complications, we examined if the expression of these transcripts changed under high glucose (HG) conditions. To do this, we examined transcript levels in HK‐2 cells, and explored the roles of ARAP1 and ARAP1‐AS2 in the EMT process in HK‐2 cells. We found increased expression of ARAP1‐AS2 and ARAP1 in HK‐2 cells under HG condition, and observed that the overexpression of ARAP1‐AS2 significantly increased the EMT process. In addition, HG upregulated Cdc42‐GTP levels in HK‐2 cells, and increased cytoskeleton rearrangement, cell viability, and migration. After knockdown of ARAP1, the level of Cdc42‐GTP was decreased; cytoskeleton reorganization, cell viability, and migration processes were decreased; and EMT and expression of fibrosis marker protein. Overall, our results indicated that ARAP1‐AS2/ARAP1 may participate in cytoskeleton rearrangement and EMT processes in HK‐2 cells through increased Cdc42‐GTP levels. Abstract : High glucose (HG) increased expression of ARAP1‐AS2 and ARAP1 in HK‐2 cells. Knockdown of ARAP1 reduced HG‐induced epithelial–mesenchymal transition (EMT) process and fibrosis by promoting the level of Cdc42‐GTP in HK‐2 cells. ARAP1‐AS2 may mediate the EMT process in HK‐2 cells by positive regulation of ARAP1.